Social support for children who had a parent killed by intimate partner violence: interviews with mental health workers - Spencer-Carver, Elaine (Kansas State University, 2008)
Children experience catastrophic loss when they have a parent killed by intimate partner violence. Their lives are immediately changed by this event. They are often left orphaned and separated from natural support systems. This study looks at the social support that children and their families have had after the death of a parent from intimate partner violence. The support is reported as seen by mental health professionals who worked with the children and their caretakers after the death. The study is a phenomenological study taken from interviews with six mental health professionals in three communities in three states. The themes found were described by at least five of the six interviewees and were also identified by a secondary rater. The themes outlined the existence of social support prior to the death as well as knowledge by the community that violence was present in the family before the murder. Stressors after the death of the parent were significant and required family re-organization. Families took steps to engage both existing and potential social supports but were often not able to utilize formal services at the time that they were offered. The importance of a consistent long-term attachment for the child was reinforced repeatedly. Grief response for both the child and the primary caretaker were complicated by the reality of the parent/son or daughter having been killed by their intimate partner. Finally, the difficulty of providing care and support for these children extracted a toll on the caretakers in their physical and mental health. Several messages emerged beyond these themes. Caretakers needed to provide emotional as well as physical care. When the emotional support was available children were able to tell the story of their experience, which they needed to do over and over again. The most problematic situations that participants described were with children who had not discussed this life event since it occurred. These children did not explore their feelings about the death of their parent or share what the loss meant to them with others.
Keywords: Intimate Partner Murder; Intimate Partner Violence; Social Support; Social Work (0452); Sociology, Individual and Family Studies (0628)